Development of Student Worksheets Based on Constructivism in Mathematics Learning for Grade VII at SMP Pertiwi 2 Padang - Sri Wahyuni; Fazri Zuzano; Listy Vermana (Pendidikan Matematika UNIMOR, 2025)
This research is motivated by the still low level of attention and participation of students during the process mathematics learning. Media used to support learning only use the Mathematics package book for class VII independent curriculum and learning is still centered on the teacher. Based on these problems, researchers developed mathematics Student Worksheets based on constructivism on quadrilateral material for class VII SMP Pertiwi 2 Padang. The aim of the research is to produce a valid and practical constructivism-based mathematics worksheet on rectangular plane material. This type of research is development research. In this study, researchers used research procedures by Borg and Gall. Data used to assess the validity of the media were obtained from validation sheets by worksheets characteristic and language experts and design experts, while the data used to assess practicality is obtained from the sheet student practicality. The worksheets developed contains flat material rectangular . The product validity assessment was carried out by two lecturers and declared valid for use from the aspects of worksheets characteristics, language and design. Practicality assessment from students' practicality questionnaire at the test stage try with practicality criteria of 77.46% based on ease of use use, ease of understanding, and time required. So it can be concluded that the constructivism-based worksheets in class VII mathematics learning at SMP Pertiwi 2 Padang is valid and practical to use as a mathematics learning medium. Based on the results of this research, researchers suggest that this worksheets can be used as an alternative media by teaching staff.